Navigated DENSE strain imaging for post-radiofrequency ablation lesion assessment in the swine left atria. Issue 1 (6th September 2013) - Schmidt, Ehud J.; Fung, Maggie M.; Ciris, Pelin Aksit; Song, Ting; Shankaranarayanan, Ajit; Holmvang, Godtfred; Gupta, Sandeep N.; Chaput, Miguel; Levine, Robert A.; Ruskin, Jeremy; Reddy, Vivek Y.; D'avila, Andre; et al.
Abstract: Aims: Prior work has demonstrated that magnetic resonance imaging (MRI) strain can separate necrotic/stunned myocardium from healthy myocardium in the left ventricle (LV). We surmised that high-resolution MRI strain, using navigator-echo-triggered DENSE, could differentiate radiofrequency ablated tissue around the pulmonary vein (PV) from tissue that had not been damaged by radiofrequency energy, similarly to navigated 3D myocardial delayed enhancement (3D-MDE). Methods and results: A respiratory-navigated 2D-DENSE sequence was developed, providing strain encoding in two spatial directions with 1.2 × 1.0 × 4 mm 3 resolution. It was tested in the LV of infarcted sheep. In four swine, incomplete circumferential lesions were created around the right superior pulmonary vein (RSPV) using ablation catheters, recorded with electro-anatomic mapping, and imaged 1 h later using atrial-diastolic DENSE and 3D-MDE at the left atrium/RSPV junction. DENSE detected ablation gaps (regions with >12% strain) in similar positions to 3D-MDE (2D cross-correlation 0.89 ± 0.05). Low-strain (<8%) areas were, on average, 33% larger than equivalent MDE regions, so they include both injured and necrotic regions. Optimal DENSE orientation was perpendicular to the PV trunk, with high shear strain in adjacent viable tissue appearing as a sensitive marker of ablation lesions. Conclusions: Magnetic resonance imaging strain may be a non-contrast alternative to 3D-MDE in intra-procedural monitoring of atrial ablation lesions.